If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3x = 0.5(14 + 6x) 7 + 3x = (14 * 0.5 + 6x * 0.5) 7 + 3x = (7 + 3x) Add '-7' to each side of the equation. 7 + -7 + 3x = 7 + -7 + 3x Combine like terms: 7 + -7 = 0 0 + 3x = 7 + -7 + 3x 3x = 7 + -7 + 3x Combine like terms: 7 + -7 = 0 3x = 0 + 3x 3x = 3x Add '-3x' to each side of the equation. 3x + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| z/7-9=3 | | t-17=20 | | 2x+5+2x+3x= | | 4(x-1)=-5(x+3)+32 | | -60x+32=Qx+p | | 5x+(2x-2)-(4x-3)= | | 3w+15=18 | | 3xy+9xy-5xy= | | 3(x-3)+2(x+2)=40 | | Y=4x^3-3x^2 | | F(x)=x^3-4x^2-5x | | 7(p+2)=-4(-4p-8) | | -2(5x+1)=-3-3x | | 3(5n-5)=-90 | | 9c=5(101)-160 | | z-10=28 | | -8(4x-3)+6x=-158 | | -8(3x+1)+5x=87 | | 91=7(-5a-2) | | 2n/3=11 | | -6(3x+5)=60 | | (9*9)-(8+4)= | | -6k+15=-5k+2k | | -10-(-63)= | | -117+4x=12x+107 | | (-5)+x=32 | | 900t-10t^2=0 | | 4(5-4x)-3x=96 | | 2(5-2x)=1.2(3x-5) | | 4(5-4x)-3x=97 | | -6(3x+4)=30 | | 2u-9=-7u |